Apeus arkistoäänitteellä : Äänellä itkeminen performanssina ja affektiivisena käytäntönä Aunuksen Karjalassa - Silvonen, Viliina (Helsingin yliopisto, 2021)
The dissertation treats the emotions of laments and the affectivity of lamenting in the context of the Olonets Karelian tradition. The analysis is based on the archival audio recordings of lament performances (approximately 460 laments) recorded in 1905–2001. In particular, the study elaborates what kinds of phenomena do we actually discuss when we discuss about emotions of laments. From the aspect of affectivity, the topic of interest concerns how lamenting and the hearing of a lament create emotional and affective experiences. The study adds the bodily aspects of emotions and affectivity, as well as the analytical perspectives of experiencing and sensing, to the previous lament research. Furthermore, the dissertation deepens understanding about the interaction of text and music in improvisatory laments, and about the relation of emotions and the composition, the performance and the structure of the lament. The dissertation presents lamenting as an affective practice and the performance of an oral tradition that is ritual by nature and conveys mythic meanings and knowledge. Text, music and emotion are treated as equal, but the study concentrates on the factors and aspects attached to emotions and affectivity. The central concepts for the analysis of the emotions of laments are experience, expression and affectivity. The affective power of laments is analysed with the concepts of an affective circle and an affective arrangement. In this study, an affective circle refers to the interactive affective relations between the factors of lament performances – for example, between the lamenter, the audience, the lament and the other world, which is always present in laments, according to the traditional mythic thinking. These circles intersect and are concurrent. The concept of the affective arrangement describes the entire constellation, which also encompasses spaces, discourses, behaviours and a range of other things and materials. The methodology is informed especially by folklore studies, cultural studies and ...